Effect of classical music and delta-wave music on sleep bruxism: a pilot study - Hosiriluck, Nattakarn; Kuertipwittaya, Manashaya; Kreesuradej, Wanwanut; Prayongpan, Somruethai; Mitrirattanakul, Somsak; Itthikul, Touch (Mahidol Dental Journal, 2024)
Objectives: To determine the effects of classical music and delta-wave music on sleep bruxism, stress, and sleep quality. Materials and Methods: Eighteen pre-clinical dental student volunteers with self-reported sleep bruxism were recruited from the Faculty of Dentistry Mahidol University. Subjects were randomly and equally divided into 3 groups: control, classical music, and delta-wave music. All participants wore T1 BruxChecker during sleep on the 1st and 2nd night and T2 BruxChecker on the 9th and 10th night. During the 3rd to 10th experimental night, subjects in both music groups listened to the assigned music track for 1 hour before bedtime using headphones, while the control group did not listen to any music. All subjects took the Suanprung stress test (SPST-20) and Pittsburgh sleep quality (PSQI) questionnaires before and after the trial period. The peeled area on BruxChecker and scores from both questionnaires were analyzed using the Wilcoxon and Kruskal-Wallis tests. Results: All experimental groups showed no statistically significant changes in the peeled area on BruxChecker during the trial. There was no statistically significant difference in the peeled area on BruxChecker among all groups. Only the classical music group showed decreasing stress levels after the trial, although not statistically significant. The delta-wave music group revealed almost statistically significant improved sleep quality (p=0.058). Conclusion: Our pilot study is the first experiment to investigate the effect of classical and delta-wave music on sleep bruxism. Although the results are still inconclusive and neither type of music significantly reduced sleep bruxism activity, listening to classical music revealed a tendency toward relieving stress and reducing sleep bruxism, whereas delta-wave music showed a tendency toward sleep quality improvement.